2020
DOI: 10.1177/0022042620931480
|View full text |Cite
|
Sign up to set email alerts
|

Decriminalized, Not Legalized: A Pilot Study of South African University Students’ Views on the Use, Impact, Legalization and Decriminalization of Marijuana

Abstract: Given the 2018 decriminalization of marijuana in South Africa for personal use and medicinal consumption, the aim of this research was to explore the perceptions of university students regarding the use, impact, legalization, and decriminalization of marijuana. Key findings revealed that a fair number of participants acknowledged using marijuana. When asked about the potential impact of marijuana on users, their families and significant others, they seemed to have a good understanding of the effects of the dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…A person who has good knowledge about drugs does not necessarily show a high resistance to drug use. The results of this study are not different from the research conducted by (Mametja and Ross, 2020), the results of their research show that adolescents who use drugs have a fairly good understanding of the impact of drug use.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…A person who has good knowledge about drugs does not necessarily show a high resistance to drug use. The results of this study are not different from the research conducted by (Mametja and Ross, 2020), the results of their research show that adolescents who use drugs have a fairly good understanding of the impact of drug use.…”
Section: Resultscontrasting
confidence: 56%
“…Similar results were also found in research (Sholihah, 2015), after counseling was carried out on the prevention and abuse of drugs, there was an increase in knowledge about the definition, type and content, and the impact of drug abuse. Drug abuse is a significant problem among adolescents in many countries, this is indicated by its high prevalence (Mametja and Ross, 2020;Patterson et al, 2020). Adolescence is a period that is very vulnerable to risky behavior, including in the case of drug abuse, this is due to high curiosity accompanied by unstable behavior both socially and emotionally.…”
Section: Resultsmentioning
confidence: 99%
“…Marijuana is the most commonly used illegal substance worldwide [ 1 , 2 , 3 , 4 , 5 ]. In recent decades, the rate of marijuana users has increased in young adults and pregnant women in the US [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-eight percent of second-year high school students indicated that they had used marijuana in the previous year and 35% of senior students indicated they used it during the year prior to 2019 [ 8 ]. The current climate of legalizing and decriminalizing marijuana use would contribute to further increments [ 3 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation